2019
DOI: 10.1016/j.tet.2019.130759
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the antioxidant capability via the synergistic effect of coupling diphenylamine with sterically hindered phenol

Abstract: Increasing the antioxidant capability via the synergistic effect of coupling diphenylamine with sterically hindered phenol. Tetrahedron, 75 (51). 130759.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Hayes's group also reported that the diphenylamine-phenol antioxidant 1 with an ethyl spacer between the diphenylamine and carboxylic acid showed an impressive oxidation induction time compared with the blend of Irganox L135 and Irganox L57. [22] Moreover, the intramolecular synergism between primary antioxidants and secondary antioxidants were also investigated. For example, Lee Hwei Voon's group synthesized several multipotent antioxidants (MPAOs) 2 which are semicarbazides and thiosemicarbazides bearing thiolated butylated hydroxytoluene (BHT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayes's group also reported that the diphenylamine-phenol antioxidant 1 with an ethyl spacer between the diphenylamine and carboxylic acid showed an impressive oxidation induction time compared with the blend of Irganox L135 and Irganox L57. [22] Moreover, the intramolecular synergism between primary antioxidants and secondary antioxidants were also investigated. For example, Lee Hwei Voon's group synthesized several multipotent antioxidants (MPAOs) 2 which are semicarbazides and thiosemicarbazides bearing thiolated butylated hydroxytoluene (BHT).…”
Section: Introductionmentioning
confidence: 99%
“…The better performance than the physical blend of two single antioxidants proved the intramolecular synergism between the phenol and diphenylamine. Hayes's group also reported that the diphenylamine‐phenol antioxidant 1 with an ethyl spacer between the diphenylamine and carboxylic acid showed an impressive oxidation induction time compared with the blend of Irganox L135 and Irganox L57 [22] . Moreover, the intramolecular synergism between primary antioxidants and secondary antioxidants were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hindered phenol and amine‐type antioxidants are the most typical representatives of primary antioxidants being extensively used in modern industry 23–25 . However, hindered phenol antioxidants show very poor antioxidant ability at evaluated temperature, which is a significant disadvantage of this type of antioxidants and greatly limits their more application in modern lubricant system 26,27 . Hence, amine‐type antioxidants have always been the research focus at present.…”
Section: Introductionmentioning
confidence: 99%
“…Since multifunctional antioxidants can possess several antioxidant functional groups in their structure, which can provide auto-synergistic antioxidant system by exhibiting radical scavenging and peroxide decomposing properties. 12,14,15 So, we envisioned to assemble several antioxidant functions in one structure by incorporating BHT moiety into semicarbazide and thiosemicarbazide compounds to obtain better antioxidant auto-synergistic effect. This article deals with the preparation and evaluation of new series of semicarbazide and its corresponding thiosemicarbazide derivatives bearing BHT moiety for their antioxidant activities using DPPH assays and DSC.…”
Section: Introductionmentioning
confidence: 99%